Review of The Fund's Income Position for FY 2022 and FY 2023-2024. (Policy Papers; Policy Paper ;, 2022)
This paper updates the projections of the Fund's income position for FY 2022 and FY 2023-2024 and proposes related decisions for the current financial year. The paper also includes a proposed decision to set the margin for the rate of charge for financial years 2023 and 2024.